Sport and character reclaiming the principles of sportsmanship - Clifford, Craig Edward 1951-; Feezell, Randolph M. 1950- (Human Kinetics, 2010)
"Unlike other books, Sport and Character : Reclaiming the Principles of Sportsmanship discusses not only how to teach sportsmanship but also why sportsmanship supports the health and welfare of individuals engaged in competitive play. Clifford and Feezell, both successful coaches and respected teachers and authors on the subject of ethics in sport, begin by offering a framework for thinking about sportsmanship. After reading a discussion of the principles of sportsmanship you'll learn how these principles can penetrate beyond the sport arena to provide guidance for everyday life."--Back cover